ИСТОКИ АФРОАМЕРИКАНСКОГО ИСЛАМА В США (Zaporizhzhia Historical Review, 2021)
The article is devoted to the origins of the African American Islam in the USA. The combination of the Black Nationalism and Islam in the first half of the 20th century created the myth according to which Islam was the primary religion of the Black man. Thanks to the nationalistic revival of the blacks in the network of Panafricanism in the early 20th century and the work of the Islamic nationalistic groups this conception has attracted many followers in the poorest citiesí areas. Nevertheless the existence of some African American Muslim organizations devoid of black nationalism shows that there are deeper roots binding the Blacks with Islam.